2021
DOI: 10.1007/s00339-021-04564-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrothermal reaction time on the supercapacitor performance of Ni-MOF nanostructures

Abstract: Metal-organic frameworks (MOFs)-based electrode materials have drawn wide interest in energy storage applications. Herein, a nickel-based metal-organic framework (Ni-MOF) has been synthesized by simple hydrothermal reaction with different reaction times. The hydrothermal reaction time has an impact on the energy storage performance of the synthesized material. Structural characterization confirms the layered structure and purity of the synthesized Ni-MOF. Significantly, improved energy storage performance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…It is also observed that the sample (1:1)s 100 °C has a longer charge and discharge time, taking a total of 660 s for a current of 1 A/g, while the sample (1:1)s 150 °C takes around 270 s, and the sample (1:1)s 200 °C takes around 250 s. Using the equation to determine the specific capacitance, namely Equation (2), we have that, for the current densities of 1 A/g, 2 A/g, 3 A/g, 4 A/g, and 5 A/g, the specific capacitances for the sample (1:1)s 100 °C are 606.63 F/g, 487.02 F/g, 303.70 F/g, 348.97 F/g, and 277.84 F/g, respectively; for the sample (1:1)s 150 °C, the values are 307.33 F/g, 239.80 F/g, 155.21 F/g, 79.74 F/g, and 20.69 F/g, respectively; and for the sample (1:1)s 200 °C, the specific capacitances are 287.42 F/g, 127.74 F/g, 40.33 F/g, 32.80 F/g, and 33.92 F/g, respectively. In this way, the best performance is obtained for the sample (1:1) at 100 °C and, despite having a lower specific capacitance according to the cyclic voltammetry curves, it is through the charge–discharge curves that there is a more representative value by becoming independent of the amount of active material used to make the working electrode [ 33 , 34 ]. It is observed that the difference in voltage given between the charge and discharge is 0.50 V for the samples (1:1)s 100 °C and (1:1)s 150 °C, while for the sample (1:1)s 200°C, the sample showed a difference of 0.52 V. Thus, the resistance R ESR can be determined, and for the samples (1:1)s 100 °C and (1:1)s 150 °C, a resistance ESR = 0.25 [Ω] is obtained, while for sample (1:1)s 200 °C, a resistance of ESR = 0.26 [Ω] is obtained, which is in accordance with what is observed in Table 1 , given that the samples (1:1) synthesized at 100 and 150 °C have a lower internal resistance compared to the samples synthesized at 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that the sample (1:1)s 100 °C has a longer charge and discharge time, taking a total of 660 s for a current of 1 A/g, while the sample (1:1)s 150 °C takes around 270 s, and the sample (1:1)s 200 °C takes around 250 s. Using the equation to determine the specific capacitance, namely Equation (2), we have that, for the current densities of 1 A/g, 2 A/g, 3 A/g, 4 A/g, and 5 A/g, the specific capacitances for the sample (1:1)s 100 °C are 606.63 F/g, 487.02 F/g, 303.70 F/g, 348.97 F/g, and 277.84 F/g, respectively; for the sample (1:1)s 150 °C, the values are 307.33 F/g, 239.80 F/g, 155.21 F/g, 79.74 F/g, and 20.69 F/g, respectively; and for the sample (1:1)s 200 °C, the specific capacitances are 287.42 F/g, 127.74 F/g, 40.33 F/g, 32.80 F/g, and 33.92 F/g, respectively. In this way, the best performance is obtained for the sample (1:1) at 100 °C and, despite having a lower specific capacitance according to the cyclic voltammetry curves, it is through the charge–discharge curves that there is a more representative value by becoming independent of the amount of active material used to make the working electrode [ 33 , 34 ]. It is observed that the difference in voltage given between the charge and discharge is 0.50 V for the samples (1:1)s 100 °C and (1:1)s 150 °C, while for the sample (1:1)s 200°C, the sample showed a difference of 0.52 V. Thus, the resistance R ESR can be determined, and for the samples (1:1)s 100 °C and (1:1)s 150 °C, a resistance ESR = 0.25 [Ω] is obtained, while for sample (1:1)s 200 °C, a resistance of ESR = 0.26 [Ω] is obtained, which is in accordance with what is observed in Table 1 , given that the samples (1:1) synthesized at 100 and 150 °C have a lower internal resistance compared to the samples synthesized at 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a charge on the whole active surface of the electrode material may be stored. Only the superficial active surface is used for charge storage at a higher scan rate because diffusion limits the passage of electrolyte ions . The area under the curve grows from 0 to 0.5 V with a broad range of scan rates from 10 to 100 mV s –1 , indicating rapid rates of ionic and electronic transport at the electrode/electrolyte interfaces.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Only the superficial active surface is used for charge storage at a higher scan rate because diffusion limits the passage of electrolyte ions. 52 The area under the curve grows from 0 to 0.5 V with a broad range of scan rates from 10 to 100 mV s −1 , indicating rapid rates of ionic and electronic transport at the electrode/electrolyte interfaces. The GCD characteristics of BDC−MOF and BTC− MOF electrodes were investigated at current densities ranging from 5 to 25 mA cm −2 in 2 M KOH electrolyte across a potential range of 0−0.5 V (Figure 10e,f).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, to overcome these shortcomings, researchers have adopted various strategies such as tuning the proportion of metal ions, 19 adjusting the pH value 20 and altering the reaction temperature and time during the synthesis of MOFs. 21,22 Additionally, regulating the solvent in the reaction system is considered to be a simple and effective method to modify MOF materials. For instance, Song et al 23 obtained an NiCo MOF with different morphologies by employing different solvents with thiophene as the ligand.…”
Section: Introductionmentioning
confidence: 99%